Development Of Self-Confidence Of Adolescents Who Abuse Drugs Through Group Guidance At The Institution Receiving Mandatory Report (IPWL) Foundation Mercusuar Pekanbaru City - Rahmad; Firman; Neviyarni (Mahir : Jurnal Ilmu Pendidikan dan Pembelajaran, 2024)
Drug abuse at the Intitusi Penerima Wajib Lapor (IPWL) Mercusuar Foundation Pekanbaru City. Group guidance can help adolescents to understand that they are not alone in facing problems and can get support from others who experience the same problems. From the results of survey observations that researchers conducted, it was found that drug abuse was by adolescents aged 17-21 years. This research aims to find out how the implementation of group guidance in developing self-confidence in adolescents who abuse drugs at the Mercusuar Foundation Recipient Institution (IPWL) Pekanbaru City. The approach used in this research is qualitative with descriptive research methods, descriptive methods are research that seeks to describe phenomena that occur in a real, realistic, actual, real way. Data is taken directly from the field through interviews with 2 addiction counselors and 3 drug abuse adolescents. From the research that has been done, it can be concluded that group guidance is effective in helping adolescents to overcome drug addiction problems by increasing self-confidence, social support, and strengthening relationships between group members at the Intitusi Penerima Wajib Lapor (IPWL) Mercusuar Foundation Pekanbaru City.